Human Rights and the Criminalization of Active Euthanasia - Tiwari, Raunak; Awasthi, Aishwarya; Bajpai, Prashant Kumar; Singh, Shivendra Kumar; Saini, Lakashya (Indian Journal of Community Health, 2025)
Euthanasia, or self- killing, is the act where an individual, who is suffering from any incurable disorder is killed without pain. There are two kinds of euthanasia i.e., active and passive. Under active euthanasia, an individual is killed directly through injecting lethal substance whereas in passive euthanasia, an individual is killed by withholding life support. In India, the Supreme Court has allowed passive euthanasia under certain circumstances as stated in Aruna Shanbaug case, but active euthanasia is still not allowed. The Court was of the view that ‘right to life’ includes ‘right to die with dignity’ but only under passive euthanasia. This paper analyses the various reasons and theories behind illegality of active euthanasia. Also, the human rights concerns that are related to the allowing of active euthanasia. The doctrinal method of research has been used in making this paper. This research methodology focuses on analysing legal principles, statutes, case laws, and legal doctrines to understand, interpret, and systematize the law. Article 21 of the Indian Constitution guarantees the ‘right to life’ which is fundamental as well as basic human right. Allowing active euthanasia can lead to violation of this basic right since it involves causing the death through an active human act i.e., injecting lethal substance.